Sport and Risk- Taking against Substance Abuse in students of Tehran High Schools - Ali Zadehmohammadi; Zohreh Ahmadabadi; Somaye Ahmadabadi; Mehdi Rafeie Borojeni (University of Tehran, 2010)
Substance abuse, violation and sexual behavior are the main reasons of fatality in adolescents and the youth. Most risky behaviors including cigarettes, alcohol, drugs and unsafe sexual contacts occur under the age of 18. Traditionally, sport is regarded as a means to encourage and develop healthy behaviors and a factor to protect and prevent risky behaviors. The present study studied 406 students including 271 male and 135 female students to compare the vulnerability of male and female athlete and non-athlete adolescents to risky behaviors such as smoking, drugs and alcohol. Iranian Adolescence Risk-Taking Scale (IARS) was used to measure the risk taking (Zadeh Mohammadi & Ahmadabadi, 2008). Those adolescents who have been a member of athletic teams had higher mean in subscale 'drinking alcohol'. Those athletes who participated in provincial competitions and higher levels, those who engaged more than three sessions a week in sport teams and those athletes who attended sport camps had a higher mean. Also, there was no significant difference between individual and group sports. When explaining the higher levels of risk-taking in those who were members of athletic teams and clubs , factors such as duality, and the difficulty in playing the role of a student and an athlete simultaneously, camp condition, lack of sufficient control over members' behaviors except when they are playing, peers' collective norms, normative pressure to conform with various expectations of the team, lack of scientific attitude towards school athletic organizations in Iran, and concurrent influence of personality features like sensation and novelty sought in tendencies toward sport and risky behaviors can be taken into account.